2014
DOI: 10.3389/fpsyg.2014.00361
|View full text |Cite
|
Sign up to set email alerts
|

Here, there and everywhere: emotion and mental state talk in different social contexts predicts empathic helping in toddlers

Abstract: A growing body of literature suggests that parents socialize early-emerging prosocial behavior across varied contexts and in subtle yet powerful ways. We focus on discourse about emotions and mental states as one potential socialization mechanism given its conceptual relevance to prosocial behavior and its known positive relations with emotion understanding and social-cognitive development, as well as parents' frequent use of such discourse beginning in infancy. Specifically, we ask how parents' emotion and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
64
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 67 publications
8
64
1
1
Order By: Relevance
“…Furthermore, this enhanced sensitivity was also reflected in increased frequency of prosocial behavior toward peers in everyday situations at nursery school, a conduct which is known to be closely related to both mental-state talk (Drummond, Paul, Waugh, Hammond, & Brownell, 2014) and EU (e.g., Brownell, Svetlova, Anderson, Nichols, & Drummond, 2013;Brownell et al, 2009;Ensor & Hughes, 2005). Nonetheless, this finding is to be interpreted with caution, as the intervention and control groups significantly differed on the pretest measure of empathy.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Furthermore, this enhanced sensitivity was also reflected in increased frequency of prosocial behavior toward peers in everyday situations at nursery school, a conduct which is known to be closely related to both mental-state talk (Drummond, Paul, Waugh, Hammond, & Brownell, 2014) and EU (e.g., Brownell, Svetlova, Anderson, Nichols, & Drummond, 2013;Brownell et al, 2009;Ensor & Hughes, 2005). Nonetheless, this finding is to be interpreted with caution, as the intervention and control groups significantly differed on the pretest measure of empathy.…”
Section: Discussionmentioning
confidence: 93%
“…Thus, before drawing final conclusions it would be necessary to replicate the research with groups showing no pretest difference on empathy scale. Furthermore, this enhanced sensitivity was also reflected in increased frequency of prosocial behavior toward peers in everyday situations at nursery school, a conduct which is known to be closely related to both mental-state talk (Drummond, Paul, Waugh, Hammond, & Brownell, 2014) and EU (e.g., Brownell, Svetlova, Anderson, Nichols, & Drummond, 2013;Brownell et al, 2009;Ensor & Hughes, 2005). Given that the teacher-guided conversations during the intervention focused not only on emotion knowledge, but also on positive social responses to others' feelings, these findings show the value of stimulating reflection on the emotional states of others and on prosocial ways of alleviating their emotional distress.…”
Section: Discussionmentioning
confidence: 99%
“…Parents increase their use of mental state language across infancy and early childhood (Beeghly, Bretherton, & Mervis, ). Research examining parent emotion and mental state talk indicates important differences evident in the second year of life that are associated with concurrent (e.g., Drummond, Paul, Waugh, Hammond, & Brownell, ; Hornik & Gunnar, ) and downstream developmental outcomes (e.g., Denham, Zoller, & Couchoud, ; Dunn, Brown, & Beardsall, ). Parent talk about emotion and mental states has been linked with a range of concurrent social skills, such as prosocial behaviors at 18‐ and 30‐months of age (Brownell, Svetlova, Anderson, Nichols, & Drummond, ), 3‐ and 5‐year‐olds emotional competence and theory of mind (LaBounty, Wellman, Olson, Lagattuta, & Liu, ; Racine, Carpendale, & Turnbull, ; Ruffman, Slade, & Crowe, ), and preschoolers' emotional understanding (Garner, Jones, Gaddy, & Rennie, ).…”
Section: Parent–child Conversations About Emotionsmentioning
confidence: 99%
“…One set of studies found that emotion talk, particularly the elicitation of emotion words [12], was correlated with behavioral assessments of young children's sharing and emotion-based helping, but not with instrumental helping [13]. Further research focused on specific social-cognitive skills and social experiences.…”
Section: Antecedents and Correlates Of Early Prosocial Actionmentioning
confidence: 99%